2022
DOI: 10.3389/fpsyg.2022.961824
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social capital on entrepreneurial resilience of SME from China: A moderated mediation model of entrepreneurial passion and Confucian traditional golden-mean thinking

Abstract: Small and medium-sized startups play a crucial role in a country's sustainable development. SMEs are at an early development stage, which means weaker institutional norms and successful paradigms, tending to suffer from exceptionally high failure rates because of many constraints, including a lack of resources and credit to access the core information. The higher the environmental uncertainty, the more likely that new start-ups rely on all kinds of social links for acquiring resources. As a critical ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 129 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…Finally, our study focuses on the joint moderating effects of environmental uncertainty, legal supervision, and Confucian culture. In contrast, the previous literature has only focused on a single market environment (Shan & Tian, 2022) or legal environment (Allen et al, 2005). We consider the current environmental situation where formal and informal institutions are intertwined, and the market environment is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study focuses on the joint moderating effects of environmental uncertainty, legal supervision, and Confucian culture. In contrast, the previous literature has only focused on a single market environment (Shan & Tian, 2022) or legal environment (Allen et al, 2005). We consider the current environmental situation where formal and informal institutions are intertwined, and the market environment is complex.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial mechanism identified is the establishment of trust and social capital within the community. Entrepreneurs who actively participate in their local communities are more likely to cultivate strong relationships, trust, and social networks (Shan & Tian, 2022). These factors, in turn, create a favorable environment for business development and sustainability.…”
Section: Community Involvement On Entrepreneurial Successmentioning
confidence: 99%
“…Studies have shown that social capital positively affects SMEs' financing as it facilitates access to finance, marketing, production, and information [14]. Social capital also affects entrepreneurial resilience by inspiring a harmonious entrepreneurial passion [15]. Financial access is another critical factor affecting SME growth.…”
Section: Introductionmentioning
confidence: 99%
“…Financial access is another critical factor affecting SME growth. Lack of seed capital raised is one of the external factors attributed to SME failures [15]. Social capital can facilitate access to external financing sources for SMEs [14].…”
Section: Introductionmentioning
confidence: 99%